Enhanced tribological performance and nanostructuring speed on AlTiN by beamshaping technology. (2nd December 2022) - Primus, T.; Hauschwitz, P.; Vitu, T.; Bičišťová, R.; Zeman, P.; Cimrman, M.; Brajer, J.; Mocek, T.; Smrž, M.
ABSTRACT: For the first time, a dynamic beamshaping technology has been utilized for the efficient production of periodic nanostructures on top of AlTiN coating to enable dry machining without costly and environmentally hazardous cutting fluids. First, a variety of periodic nanostructures with periods in a range of 740–273 nm were produced utilizing different wavelengths. Additionally, beamshaping technology increased productivity by 4008% up to 105 cm 2 min −1 by shaping the Gaussian beam into a rectangular beam of 500 × 30 µm. To simulate the application load and resulting heat production during manufacturing, friction analysis was performed at room and elevated temperature to 500°C. The analysis revealed a significant reduction in the friction coefficient – up to 27% and 19% at room temperature and 500°C, respectively. The combination of these results demonstrates that the proposed method can be scaled up for the mass production of functionalized machining tools for dry machining.